Hyperosmotic Infusion and Oxidized Surfaces Are Essential for Biofilm Formation of Staphylococcus capitis From the Neonatal Intensive Care Unit - Qu, Yue; Li, Yali; Cameron, David R.; Easton, Christopher D.; Zhu, Xuebo; Zhu, Minli; Salwiczek, Mario; Muir, Benjamin W.; Thissen, Helmut; Daley, Andrew; Forsythe, John S.; Peleg, Anton Y.; et al. (Frontiers in Microbiology, 2020)
Staphylococcus capitis is an opportunistic pathogen often implicated in bloodstream infections in the neonatal intensive care unit (NICU). This is assisted by its ability to form biofilms on indwelling central venous catheters (CVC), which are highly resistant to antibiotics and the immune system. We sought to understand the fundamentals of biofilm formation by S. capitis in the NICU, using seventeen clinical isolates including the endemic NRCS-A clone and assessing nine commercial and two modified polystyrene surfaces. S. capitis clinical isolates from the NICU initiate biofilm formation only in response to hyperosmotic conditions, followed by a developmental progression driven by icaADBC expression to establish mature biofilms, with polysaccharide being their major extracellular polymer substance (EPS) matrix component. Physicochemical features of the biomaterial surface, and in particular the level of the element oxygen presented on the surface, significantly influenced biofilm development of S. capitis. A lack of highly oxidized carbon species of the surface prevented the immobilization of S. capitis EPS and formation of mature biofilms. This information provides guidance in regards to the preparation of hyperosmolar total parenteral nutrition and the engineering of CVC surfaces that can minimize the risk for catheter-related bloodstream infections caused by S. capitis in the NICU.